BUREAUCRATIC BEHAVIOR RELATED WITH PROVIDING OF PUBLIC SERVICES IN REGIONAL CAPITAL INVESTMENT - PRIHATI, PRIHATI (Human Sustainability Procedia, 2018)
The objective of this research is to reveal and analyze bureaucratic behavior related with providing of public services in regional capital investment. The method used in this research is descriptive qualitative, which aims to bureaucratic behavior related with providing of public services in regional capital investment. The data collection used, as common in qualitative research are observation, interviews and documentation. The collected data were analyzed with interactive model of Miles and Huberman. The research result indicated thatall components and sub-components of bureaucratic behavior of Investment Coordinating and IntegratedLicensing Board (BKPMPT), in terms of work obedience, job persistence, responsibility, job satisfaction, and discipline are in the minimal category in the providing of public services. The results of this assessment indicate the importance of BKPMPT to keep improving continuously on the sub-components and components of bureaucratic behavior that tend to be in the lower limit classification. Based on the results of the analysis, it appears that some components and sub-components of bureaucratic behavior in public services need to be improved. the components needs to be improved are the component of job satisfaction, which includes: job satisfaction, satisfaction over environmental conditions and office facilities, and satisfaction on compensation (remuneration). Restoration or improvemment the quality of bureaucratic behavior for job satisfaction is important. The expectation of job satisfaction can improve employee performance